Types of Student's Speech Actions in Response to Tea-cher's Learning Strategy - Putra, Naufal Erlangga; Markhamah, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to determine the types of speech acts used by students responding to learning strategies used by teachers. To find out and describe the forms of speech acts used by students responding to learning strategies used by teachers. Methodology: This research uses a qualitative descriptive approach, with data sources from interviews with students. The data collection techniques used in this research are interviews, listen freely and engage in conversation (SBLC), record, and note. After the data were collected, the data were analy-zed by (1) Analyzing raw data from students in the form of interview results, (2) identifying data based on types of speech acts, and forms of speech (3) classifying data based on types of speech acts, and forms of speech, (4) ana-lyzing data based on types of speech acts, and forms of speech, (5) conclu-ding data based on data collection. First, the type of speech acts used by stu-dents is assertive illocutionary speech acts. Results: First, the type of speech acts used by students is assertive illocutionary speech acts. Second, the forms of students' speech acts found are stating 4 speech acts, reinforcing 2 speech acts, informing/announcing 3 speech acts, expressing opinions 5 speech acts. Applications/Originality/Value: Based on the results of the research, the main points of this study are the types of speech acts used, namely assertive speech acts, the forms of speech used by students are four forms of speech.